METHODOLOGY OF USING MOBILE APPLICATIONS IN SPORTS TRAINING - Ashirboyev I. M. (Modern American Journals, 2025)
This article explores modern methodological approaches to using mobile applications in sports training. It highlights the role of digital technologies in monitoring athletes’ physical preparedness, individualizing training processes, and analyzing performance results. The advantages of fitness and sport-monitoring applications, as well as methods for their integration into the educational process, are discussed. The research findings are aimed at assisting sports teachers, coaches, and students in the digitalization of training activities and improving their effectiveness.
Keywords: Mobile applications, sports training, digital technologies, methodology, fitness monitoring, physical preparedness, educational process.